Transferrin mutations at the glycosylation site complicate diagnosis of congenital disorders of glycosylation type I - Guillard, Mailys (Springer Netherlands, 2011)
Congenital disorders of glycosylation (CDG) form a group of metabolic disorders caused by deficient glycosylation of proteins and/or lipids. Isoelectric focusing (IEF) of serum transferrin is the most common screening method to detect abnormalities of protein N-glycosylation. On the basis of the IEF profile, patients can be grouped into CDG type I or CDG type II. Several protein variants of transferrin are known that result in a shift in isoelectric point (pI). In some cases, these protein variants co-migrate with transferrin glycoforms, which complicates interpretation. In two patients with abnormal serum transferrin IEF profiles, neuraminidase digestion and subsequent IEF showed profiles suggestive of the diagnosis of CDG type I. Mass spectrometry of tryptic peptides of immunopurified transferrin, however, revealed a novel mutation at the N-glycan attachment site. In case 1, a peptide with mutation p.Asn630Thr in the 2nd glycosylation site was identified, resulting in an additional band at disialotransferrin position on IEF. After neuraminidase digestion, a single band was found at the asialotransferrin position, indistinguishable from CDG type I patients. In case 2, a peptide with mutation p.Asn432His was found. These results show the use of mass spectrometry of transferrin peptides in the diagnostic track of CDG type I.